Androgen actions in mouse wound healing: Minimal in vivo effects of local antiandrogen delivery. Issue 3 (6th May 2016) - Wang, Yiwei; Simanainen, Ulla; Cheer, Kenny; Suarez, Francia G.; Gao, Yan Ru; Li, Zhe; Handelsman, David; Maitz, Peter
Abstract: The aims of this work were to define the role of androgens in female wound healing and to develop and characterize a novel wound dressing with antiandrogens. Androgens retard wound healing in males, but their role in female wound healing has not been established. To understand androgen receptor (AR)‐mediated androgen actions in male and female wound healing, we utilized the global AR knockout (ARKO) mouse model, with a mutated AR deleting the second zinc finger to disrupt DNA binding and transcriptional activation. AR inactivation enhanced wound healing rate in males by increasing re‐epithelialization and collagen deposition even when wound contraction was eliminated. Cell proliferation and migration in ARKO male fibroblasts was significantly increased compared with wild‐type (WT) fibroblasts. However, ARKO females showed a similar healing rate compared to WT females. To exploit local antiandrogen effects in wound healing, while minimizing off‐target systemic effects, we developed a novel electrospun polycaprolactone (PCL) scaffold wound dressing material for sustained local antiandrogen delivery. Using the antiandrogen hydroxyl flutamide (HF) at 1, 5, and 10 mg/mL in PCL scaffolds, controlled HF delivery over 21 days significantly enhanced in vitro cell proliferation of human dermal fibroblasts and human keratinocytes. HF‐PCL scaffolds also promoted in vivo wound healing in mice compared with open wounds but not to PCL scaffolds.